Mission San Carlos Borromeo and ruins - Tucker, John O., d. 1928 (photographer):::Creator::::::::::::
Panoramic view of Mission San Carlos Borromeo and the ruins of another building. This is also known as Mission Carmel. Three women and a man are looking at the mission in the foreground, with a small house among the hills in the background.